Autocicatrização do concreto com diferentes tipos de cimentos em interação com catalizador cristalino - Pedroso, Maria Goreti (2019)
In a concrete structure, there are microcracks and cracks that have expected or unexpected characteristics. These microcracks may will be the way to external agents with degradation effect. For this reason, there is a need to control the concreting process and the use of materials improving concrete characteristics, among them the durability. So, there is a demand for materials that spontaneously or stimulated, embedded in the concrete, can contribute to self-healing. Among the possibilities of increase durability are cementitious materials contributing to the closing of cracks and pores, which can be added in a concrete. Corroborating with researches, in this dissertation will be analyzed the selfhealing with cements CP II-F-40, CP III-40-RS and CP V-ARI in interaction with crystalline catalyst. Tests of resistance to axial compression were made and showed alteration of the results which the use of the crystalline catalyst, and the capillary absorption tests showed an efficiency in the use of the crystalline catalyst. And, the PVA fiber also presented changes regarding selfhealing results for the three cements of this research.